2020
DOI: 10.1021/acsnano.0c04397
|View full text |Cite
|
Sign up to set email alerts
|

Up- and Down-Conversion between Intra- and Intervalley Excitons in Waveguide Coupled Monolayer WSe2

Abstract: The presence of two spin-split valleys in monolayer (1L) transition metal dichalcogenide (TMD) semiconductors supports versatile exciton species classified by their spin and valley quantum numbers. While the spin-0 intravalley exciton, known as the “bright” exciton, is readily observable, other types of excitons, such as the spin-1 intravalley (spin-dark) and spin-0 intervalley (momentum-dark) excitons, are more difficult to access. Here we develop a waveguide coupled 1L tungsten diselenide (WSe2) device to pr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 45 publications
(74 reference statements)
2
15
0
Order By: Relevance
“…Additionally, despite the seemingly simplistic single-particle picture presented here, these results also provide an explanation for the recently observed asymmetry between bright and dark excitons concerning direct to indirect exciton scattering in W-based TMDs [36], where indirect excitons are composed of an electron and a hole in opposite valleys.…”
Section: Acoustic Phononssupporting
confidence: 53%
“…Additionally, despite the seemingly simplistic single-particle picture presented here, these results also provide an explanation for the recently observed asymmetry between bright and dark excitons concerning direct to indirect exciton scattering in W-based TMDs [36], where indirect excitons are composed of an electron and a hole in opposite valleys.…”
Section: Acoustic Phononssupporting
confidence: 53%
“…These transitions strongly couple to light via in-plane ( x – y direction) dipoles, 19 making the A b -, B b -channels the dominant features in conventional photoluminescence (PL) spectrum. Interestingly, the main PL emission channel in TMDs arises from the A b -exciton, 2,20 where to date, limited increase of the B b -exciton emission signal was realized by several factors such as pump intensity, 21 substrate, 22 sample quality, 23 and bright-to-bright exciton mixing 24 (see ESI† note 1). Nonetheless, an all-optical way enabling strong modulation between the two bright excitonic channels can pave the way for exciting tunable multi-wavelength devices.…”
Section: Introductionmentioning
confidence: 99%
“…We found that 2 for the X exciton is > 74%, even higher than the analogous process in carbon nanotubes (CNTs; < 40%) 29 , suggesting that the dark exciton in 1L-WSe2 behaves as a significant reservoir of X exciton emission through efficient inter-state upconversion. 24…”
Section: Time-resolved Photoluminescence Of the High-quality Hbn-encamentioning
confidence: 99%
“…As a result, the energy of a photon emitted by the XK exciton is 61 meV below the X exciton emission, even lower than D exciton. [21][22][23][24] In this work, by measuring the time-resolved photoluminescence (Tr-PL) of the high-quality hexagonal boron nitride (hBN) encapsulated 1L-WSe2 at cryogenic temperature, we observe dense populations of D and XK excitons with sub-ns lifetime.…”
mentioning
confidence: 99%